Prevalence and Antibiotic Resistance of Salmonella spp. Isolated from Environment and Livestock at a Community in Sri-Racha District, Chonburi Province - Nakbubpa, Kulchai; Sasiwat, Pennipach; Klebkasorn, Tamonwan; Pudphai, Unchalee; Pornsukarom, Suchawan (Journal of Mahanakorn Veterinary Medicine, 2022)
This study was proceeded with objective for studying prevalence, and comparing antibiotic resistance of Salmonella spp. isolated from environment and livestock in Sri-Racha District, Chonburi Province, Thailand. Taking 300 samples in May 2018 to March 2019, including 73 samples of livestock feces and 227 samples from environment around livestock farms, to bacterial isolation and antibiotic susceptibility determination by disc diffusion method. From result of this study, Salmonella spp. in a chicken fecal sample was found, which as 0.33% of all samples, and the serovar was Salmonella Kentucky, but did not found any bacteria in environmental samples, which assumed that this bacteria had least detected in this community. In addition, antibiotic susceptibility determination had resistance to Ampicillin, Penicillin, Cephalexin, and Amoxicillin which considered as multidrug resistance (MDR) isolate.